Berat Lahir Rendah, Jenis Kelamin Anak, Jumlah Anak dan Pendidikan Ibu Sebagai Faktor Risiko Stunting di Kota Palu - Indonesia: Low Birth Weight, Child Gender, Number of Children, and Maternal Education as Risk Factors for Stunting in Palu City - Indonesia - Hafid, Fahmi; Nasrul, Nasrul; Amsal, Amsal; Ramadhan, Kadar; Taufiqurahman, Taufiqurahman; Sariman, Sarina (Amerta Nutrition, 2024)
Background: The worldwide issue of stunting, which is prevalent up to 20.5%, can have an impact on future productivity and health Objectives: to determine the risk factors and prevalence of stunting in children aged 0-23 months in Palu City, Indonesia. Methods: This study used a cross-sectional analytical design in eight sub-districts of Palu City (January-June 2024), involving 516 pairs of mothers and children aged 0-23 months. Data were collected by 20 enumerators under the supervision of the Health Office, through interviews related to breastfeeding, complementary feeding, infection history, and other variables as well as anthropometric measurements using length Board Measuring calibrated tools. The data were analyzed using univariate analysis, chi-square test bivariate, and logistic regression. Data collection is carried out through the Cobocollect platform. Results: Logistic regression analysis shows several important findings. Children of mothers with low education (OR=1.9), male children (OR=2.2), low birth weight (OR=3.1), and families with more than 3 children (OR=2.1) have a higher risk of stunting. Of the 516 children, 20.5% experienced stunting. These findings highlight the importance of maternal education, gender, birth weight, and number of children as risk factors for stunting, as well as their implications for health policies. Conclusions: Factors such as low birth weight, male sex, the number of children over three, and mothers' education of less than 9 years significantly increased the risk of stunting in children. Targeted nutrition interventions for mothers with low education and families with many children are essential to reduce the prevalence of stunting in Palu City.